Sistem Pelaporan Parkir Liar Berbasis Geolocation di Kota Denpasar - Saputra, Aggry; Sudarma, Made; Wiharta, Dewa Made (Majalah Ilmiah Teknologi Elektro, 2019)
Every  year,  the  number  of  vehicles  is  increasing due   to   the   development   of   the   population,   economy   and improvement in living standard. Although there are parking lots, there  are  still  many  drivers  who  park  their  vehiclesin  places where   they   can   disrupt   the   smooth   flow   of   traffic.   The application  of  a  parking reporting  system uses the Google Maps API  to  mark  areas  and  get  coordinates  for  reporting  illegal parking.  The  process  of  marking  the  parking  ban  area  uses  the polygon method with the number of roads as test data as many as 14 street names, 25 parking ban areas and 100 coordinate points (latitude,  longitude).  Every  report  on  illegal  parking  has  images and  coordinates  of  location  reporting  that  will  automatically  be validated  by  the  system.  The  validation  process  by  the  system uses  the  JavaScript  API  Geometry  library  to  get  the  results  of whether  a reported  vehicle is in the  parking  ban  area. Of the 12 coordinate  points  randomly  placed  with  6  positions  insidethe parking ban area and 6 outside the parking ban area, the system is ableto validate the data correctly.